Applied Different Pixel Selection in METRIC Model for Estimating Spatial Daily Evapotranspiration of Oil Palm in East Kalimantan Province, Indonesia - Dhohir, Nur Muhammad Abdul; June, Tania (UNIB Press, 2023)
Determination of evapotranspiration (ET) plays a key role in managing water in oil palm plantations. Several energy balances models have been developed for mapping evapotranspiration regionally. Subsequently, this study aims to estimate daily evapotranspiration in oil palm plantation using the METRIC model, where pixel selection used and corrected by hot and cold pixels. The climate data were collected from ERA-5 Reanalysis and Landsat 8 was used for spatial analysis. The result depicts the means ± standard deviation of ET without pixel selection (with pixel selection), specifically for oil palms age of 4, 6, 7, 8, 9, 11, 12 and 13 years were 3.19 ± 1.62 mm d-1, 3.31 ± 1.14 mm d-1, 4.01 ± 0.96 mm d-1, 4.84 ± 0.87 mm d-1, 6.29 ± 0.43 mm d-1, 5.72 ± 0.44 mm d-1, 6.43 ± 0.23 mm d-1 and 6.21 ± 0.33 mm d-1 (4.22 ± 0.49 mm d-1, 3.99 ± 0.22 mm d-1, 2.96 ± 0.34 mm d-1, 3.14 ± 0.33 mm d-1, 4.22 ± 0.49 mm d-1, 3.99 ± 0.22 mm d-1, 4.26 ± 0.24 mm d-1 and 4.18 ± 0.30 mm d-1), respectively. We have found more accurate ET determination with pixel selection (higher coefficient of determination).